(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هدف البحث إلى التعرف على مدى التزام مدققي الحسابات الأردنيين بمتطلبات معيار التخطيط رقم (300), كذلك معرفة التزام مدققي الحسابات الأردنيين بمعرفة أعمال العميل محل التدقيق وتطبيق مفهوم الأهمية النسبية في مرحلة تخطيط عملية التدقيق الإلكتروني. بناءً على اختبار الفرضيات وتحليل النتائج فقد توصل البحث الى عدد من النتائج كان من أهمها, أن هناك التزاماً من قبل مدققي الحسابات الأردنيين بمتطلبات المعيار (300) في ظل التدقيق الإلكتروني, كذلك يقوم مدققو الحسابات الأردنيين بمعرفة أعمال العميل محل التدقيق الإلكتروني. وقد أوصى البحث بضرورة عقد الدورات من قبل جمعية المحاسبين القانونيين الأردنيين لتوعية مدققي الحسابات الأردنيين بأهمية التدقيق الإلكتروني وما يعود به من فائدة على الأطراف ذات العلاقه. The study aimed to identify the commitment of Jordanian auditors to the requirements of standard No. (300), as well as commitment of Jordanian auditors knowledge of the client, and the application of the materiality concept in the planning phase of the electronic auditing process. Based on hypothesis testing and analysis of the results, research has come to a number of results, the most important was that there is a Commitment by the Jordanian auditors to the requirements of the international auditing standard no (300) under electronic audit, as well as the Jordanian auditors commitment of knowledge of the client under electronic audit. The study recommended that the sessions should be held by the Jordanian chartered accountants association to raise awareness among Jordanian auditors to the importance of electronic auditing and its usefulness to the Parties.